Model Transfer Anggaran Kabupaten Berbasis Ekologi (TAKE) dalam Implementasi Program Siak Hijau Mencapai Pembangunan Berkelanjutan di Kabupaten Siak Provinsi Riau - Agus Mandar; Wan Muhammad Yunus; Ali Asfar; Nadia Marshanda (Jurnal Zona, 2026)
The Sustainable Development Goals (SDGs) are a concept that has been agreed upon and committed to by the global community to be implemented by countries around the world, to be achieved by 2030 at the latest. The Indonesian government has ratified this agreement by issuing Presidential Regulation No. 111 of 2022 and drafting the 2025–2029 SDGs National Action Plan, which emphasises strategic coordination, integrated monitoring, and financing innovation. These regulations are followed up at the subnational level by both provincial and district/city governments, down to the village/sub-district level. At the provincial level, Riau has launched the Riau Hijau (Green Riau) Programme through Riau Governor Regulation No. 9 of 2021, which serves as a guideline for environmentally-friendly development in Riau Province. This regulation supports the reduction of greenhouse gas emissions and the improvement of environmental quality. At the Siak Regency Government level, the Siak Hijau (Green Siak) Programme has been issued through Regional Regulation No. 4 of 2022, which serves as the legal basis for the implementation of environmentally-based sustainable development in Siak Regency. This regional regulation establishes strategies, policies, and mechanisms for implementing Siak as a Green Regency. As an implementation and strategy of the Siak Regency Government in accelerating the implementation of the Siak Green Programme to achieve the Sustainable Development Goals (SDGs), the Siak Regency Government has established a Green Siak Task Force